Genetic analysis of anthracnose resistant and heat tolerant chili inbreed lines based on morpho-physiological characteristics - Chowdhury, Mst. Farhana Nazneen; Rafii, Mohd Y.; Ismail, Siti Izera; Ramlee, Shairul Izan; Hosen, Monir; Rezaul Karim, K.m.; Yusuff, Oladosu; Ridzuan, Raihana (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2023)
A better understanding of the various desirable characteristics present in chili (Capsicum annuum L.) genotypes has aided in developing more effective selection methods for crop improvement. Identifying genetically superior parents is critical in selecting the best parents and inbred lines for breeding purposes. This study was conducted over two planting seasons in glasshouse using morpho-physiological parameters to evaluate the heritability variation of selected chili genotypes based on their genetic diversity for future breeding program. Significant variances were observed in all the studied parameters across the chili pepper accessions with an inclusive range of diversity. The highest genotypic coefficient of variation (≥ 20%) was observed for all physiological and yield characteristics. While the highest phenotypic coefficient of variation (≥ 20%) was seen for all examined characteristics. All studied parameter had high broad sense heritability (˃ 55%) except total number of branches per plant (47.9%) while the moderate to high genetic advance were observer for all studied traits demonstrating that the extents of heritability and variability are due to their genetic makeup and environment had little influence on these characters. The evaluated genotypes were grouped into seven clusters based on the cluster analysis and Group I recorded highest yield with eight genotypes while Groups III, IV, V, VI, and VII recorded one each. Plant height and total branch number showed a highly significant positive correlation with the number of fruits per plant and yield per plant. Similarly, the number of fruits per plant had a highly significant positive correlation with fruit yield per plant. The study revealed that genetic variability might be usefully exploited through selection for further breeding purposes to increase yield and production.